Low cost bench scale apparatus for measuring the thermal resistance of multilayered textile fabric against radiative and contact heat transfer. (April 2019) - Shaid, Abu; Wang, Lijing; Padhye, Rajiv; Gregory, Martin
Graphical abstract: Abstract: Radiation is the main medium of heat transfer from fire to firefighter. The protective clothing a firefighter wears is required to have good capability to resist this incoming heat radiation. Various fibre, fabric and other materials offer different levels of protection against heat radiation. The instruments used to measure the protective capability of fabric against radiant heat are normally expensive and may unable to measure heat resistance behind each layer of a multilayer combination simultaneously. In the current study, a bench scale and easy-to-operate instrument has been developed to measure the radiative and contact heat protection performance of textile fabric/clothing in multilayered configurations. Normal wooden frames, domestic aluminum foil, free open source software and high precision temperature sensors are used to develop the instrument. This instrument can be a very useful tool to gain primary understanding of the radiative heat protection of any material in single or multilayered configuration.